Microstructure-related in vitro bioactivity of a natural ceramic of Saxidomus purpuratus shell. (5th February 2018) - Wang, Xu; Ji, Hong-Mei; Li, Xiao-Wu
Abstract: To explore some new approaches to designing novel mimetic architecture for bone implant materials, the conversion of a natural ceramic of Saxidomus purpuratus shell to hydroxyapatite (HAp) was investigated in the present study by using a pre-treatment in phosphate buffer solution (PBS) and an in vitro assessment in stimulated body fluid (SBF) solution. The main concern was focused on a comparison of in vitro bioactivity on the outer layer (porous fibrous/blocky structure) and inner layer (complex crossed-lamellar) of the shell. It is found that the apatites are deposited more compactly on the surface of porous blocky layer than crossed-lamellar layer in the preliminary stage of immersion in PBS for the same time. However, after a subsequent in vitro mineralization in SBF for a relatively long time of 4 weeks, the bioactive bone-like apatite layers are formed on the both inner and outer layers with different structures. Importantly, the results have demonstrated that the crossed lamellar structure with a good combination of mechanical and biological performances can be well referenced as a bio-inspired composite structure for hard tissue replacements. Graphical abstract: Highlight: Shell microstructure affects the conversion ability of aragonites into hydroxyapatite in phosphate buffer solution. Apatites are deposited more compactly on the outer layer than inner layer in phosphate buffer solution. Different microstructural layers of shell exhibit a comparable in vitro bioactivity in stimulated body fluid. A bionic structure design is raised for biomaterials for hard tissue replacement.